Bridging the gap: assessing CMV DNAemia in kidney transplant recipients with previous solid organ transplants - Katz-Greenberg, Goni; Steinbrink, Julie M.; Shah, Krishna; Byrns, Jennifer S. (Frontiers in Transplantation, 2024)
Cytomegalovirus (CMV) infection poses a significant threat to solid organ transplant (SOT) recipients and can lead to various complications and adverse outcomes. In an effort to prevent CMV infection, it is common to utilize prophylactic strategies to prevent CMV infection, such as valganciclovir, especially for high-risk patients. Risk factors for CMV infection in kidney transplant recipients (KTRs) include CMV mismatch between donor and recipient), and intensity of immunosuppression such as use of T-cell depleting agents. However, little attention has been given to KTRs with a history of prior SOTs, despite their prolonged exposure to immunosuppressive regimens. This retrospective single-center study aimed to investigate the incidence and implications of CMV DNAemia in KTRs with prior SOTs. The study included 97 KTRs with prior SOTs and 154 KTRs with no prior transplants as a control group. Patients in the KTRs with prior SOT were more sensitized than the control group [cPRA > 30%: 49 patients (50.5%) vs 30 (19.45%), p=0.001]. There was a 39.2% incidence of CMV DNAemia in the previous SOT group compared to 48.7% in the control group (NS). Patients with prior SOTs demonstrated a shorter time to CMV DNAemia post-transplant [median time of 1.6 months (IQR 0.7, 5.8) in the KTRs with prior SOTs versus 2.6 months (IQR 1.5, 8.1) in the control group (p=0.001)]. Despite its limitations, this study underscores the importance of recognizing the heightened risk of CMV infection or reactivation in KTRs overall and the potential benefits of proactive intervention to mitigate associated morbidity and mortality.